Tindak Pidana Pencurian Kendaraan Roda Dua Yang Dilakukan Secara Bersama-Sama - Derry Aris Munandar; Airi Safrijal (Jurnal Hukum dan Keadilan "MEDIASI", 2018)
Theft is regulated in Article 362 through Article 367 of the Indonesian CriminalCode (KUHP). In this study specifically the criminal act of theft which is aggravated as stipulated in Article 363 paragraph (1) point 3, point 4 and point 5 and paragraph (2). The causes of motorcycle crime are carried out jointly because of economic factors, educational factors, individual factors, and environmental factors. The application of the criminal act against the perpetrators has not yet run maximally because the sentence imposed is still very mild with the defendant regretting his actions, promising not to repeat his actions, being polite, being straightforward in court, and having never been convicted therefore the judge must give the punishment according to the consequences of the theft can harm others.